Vindoline Attenuates Osteoarthritis Progression Through Suppressing the NF-κB and ERK Pathways in Both Chondrocytes and Subchondral Osteoclasts - Zhu, Meisong; Xu, Qiang; Yang, Xinmin; Zhan, Haibo; Zhang, Bin; Liu, Xuqiang; Dai, Min (Frontiers in Pharmacology, 2022)
Disruption of extracellular matrix (ECM) homeostasis and subchondral bone remodeling play significant roles in osteoarthritis (OA) pathogenesis. Vindoline (Vin), an indole alkaloid extracted from the medicinal plant Catharanthus roseus, possesses anti-inflammatory properties. According to previous studies, inflammation is closely associated with osteoclast differentiation and the disorders of the homeostasis between ECM. Although Vin has demonstrated effective anti-inflammatory properties, its effects on the progression of OA remain unclear. We hypothesized that Vin may suppress the progress of OA by suppressing osteoclastogenesis and stabilizing ECM of articular cartilage. Therefore, we investigated the effects and molecular mechanisms of Vin as a treatment for OA in vitro and in vivo. In the present study, we found that Vin significantly suppressed RANKL-induced osteoclast formation and obviously stabilized the disorders of the ECM homeostasis stimulated by IL-1β in a dose-dependent manner. The mRNA expressions of osteoclast-specific genes were inhibited by Vin treatment. Vin also suppressed IL-1β-induced mRNA expressions of catabolism and protected the mRNA expressions of anabolism. Moreover, Vin notably inhibited the activation of RANKL-induced and IL-1β-induced NF-κB and ERK pathways. In vivo, Vin played a protective role by inhibiting osteoclast formation and stabilizing cartilage ECM in destabilization of the medial meniscus (DMM)-induced OA mice. Collectively, our observations provide a molecular-level basis for Vin’s potential in the treatment of OA.